2022
DOI: 10.1016/j.annepidem.2021.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatially refined time-varying reproduction numbers of SARS-CoV-2 in Arkansas and Kentucky and their relationship to population size and public health policy, March – November 2020

Abstract: Purpose To examine the time-varying reproduction number, R t , for COVID-19 in Arkansas and Kentucky and investigate the impact of policies and preventative measures on the variability in R t . Methods Arkansas and Kentucky county-level COVID-19 cumulative case count data (March 6-November 7, 2020) were obtained. R t was estimated using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…40 Politis et al found facemask mandate was associated with a decrease in R t by 11% and 6%, respectively, in Arkansas and Kentucky. 10 Thus, our findings in South Carolina are consistent with findings in other states that a mask mandate was associated with slowing epidemic growth.…”
Section: Discussionsupporting
confidence: 90%
“…40 Politis et al found facemask mandate was associated with a decrease in R t by 11% and 6%, respectively, in Arkansas and Kentucky. 10 Thus, our findings in South Carolina are consistent with findings in other states that a mask mandate was associated with slowing epidemic growth.…”
Section: Discussionsupporting
confidence: 90%
“…We performed R e estimation analysis using the "EpiEstim" package [94]. Researchers have widely used this package to determine the epidemic trajectory in different settings [34,91,95].…”
Section: Epidemic Trajectory Analysismentioning
confidence: 99%
“…This should not be unexpected since Iran is the epicentre of the pandemic in the Middle East. In the United States,Politis et al (2022) investigated the timevarying reproduction number in Arkansas and Kentucky, reporting peak values of 1.15 and 1.10, respectively. These lower values were achieved through policies and measures that effectively slowed transmission of the pandemic(Politis et al, 2022) From pandemic onset, age and gender have been identified as significant risk factors(Goldstein et al, 2021;…”
mentioning
confidence: 99%
“…This should not be unexpected since Iran is the epicentre of the pandemic in the Middle East. In the United States,Politis et al (2022) investigated the timevarying reproduction number in Arkansas and Kentucky, reporting peak values of 1.15 and 1.10, respectively.CONCLUSSIONIt is apparent that COVID-19 pandemic has passed, especially with the recent declaration by WHO Director-General (WHO, 2023) that COVID-19 is no longer a public health emergency of international concern, and the follow-up statement issued by the NCDC (NCDC, 2023). However, with international travelling restrictions lifted and COVID-19 protocols relaxed, both WHO and the NCDC cautioned that the dangers posed by the virus still remains within communities and hence a significant risk of transmitting a strain or new variants across the globe.…”
mentioning
confidence: 99%
See 1 more Smart Citation